Behcet's Disease - Gonul, Muzeyyen; Pelin Kartal, Selda (IntechOpen, 2017)
Behcet's disease is a multisystem inflammatory disease with unknown etiology and has a unique geographic distribution. It is characterized by recurrent oral aphthous lesions, recurrent uveitis, skin lesions, and genital ulcerations. However, it may involve the eye, joints, and cardiovascular, gastrointestinal, and neurological systems at varying degrees as well as the skin and mucous membranes. The disease may manifest itself in a wide spectrum of symptoms ranging from mild symptoms to life-threatening symptoms or severe symptoms that may create permanent sequelae. Knowing the nature of the disease will make it easier to diagnose and manage the disease. This book was written by expert authors, and detailed epidemiology, etiopathogenesis, mucocutaneous findings, and systemic involvement of Behcet's disease are presented to readers.